KEPATUHAN PAJAK BAGI WAJIB PAJAK ORANG PRIBADI DI KABUPATEN NGANJUK - Ambar - Wati (AKUNTANSI DEWANTARA, 2018)
AbstractThis study aims to test and prove the influence of internal factors, external factors, perceptions of taxpayer compliance of individuals with certain circulation in Nganjuk district and to test and prove the influence of internal factors and external factors on taxpayer compliance through perception. And to test and prove the influence of internal factors and external factors on perception.The population of this study is 1.744 individual taxpayers located in Nganjuk. The technique of collecting the sample using accidental sampling method, so get 100 respondents. Data analysis techniques using WarpPLS, an application that can estimate the relationship between latent variables whether linear or non linear.The results of this study indicate that internal factors and external factors are not able to give a positive effect on perception. Internal factors are not able to give a positive effect on taxpayer compliance, but external factors and perception can give a positive effect on taxpayer compliance. Internal factors and external factors are not able to give a positive effect on taxpayer compliance through perception.Keywords: internal, external, perception, and taxpayer compliance.